?-Statistically Convergent and ?-Statistically Bounded Sequences Defined by Modulus Functions - Ibrahim, Ibrahim S.; Colak, Rifat (Soc Paranaense Matematica, 2024)
In this research paper, we introduce some concepts of lambda f -density in connection with modulus functions under certain conditions. Furthermore, we establish some relations between the sets of lambda f -statistically convergent and lambda f -statistically bounded sequences.
Keywords: Density; modulus function; lambda-Statistical convergence